Emulsion electrospinning of sodium alginate/poly(ε-caprolactone) core/shell nanofibers for biomedical applications. Issue 13 (14th June 2022) - Norouzi, Mohammad-Reza; Ghasemi-Mobarakeh, Laleh; Itel, Fabian; Schoeller, Jean; Fashandi, Hossein; Borzi, Aurelio; Neels, Antonia; Fortunato, Giuseppino; Rossi, René M.
Abstract : Sodium alginate/poly(ε-caprolactone) core/shell nanofibers were fabricated via water-in-oil emulsion electrospinning. The sodium alginate concentration, water-to-oil ratio, and surfactant concentration were optimized for the maximum stability. Abstract : Electrospun nanofibers have shown great potential as drug vehicles and tissue engineering scaffolds. However, the successful encapsulation of multiple hydrophilic/hydrophobic therapeutic compounds is still challenging. Herein, sodium alginate/poly(ε-caprolactone) core/shell nanofibers were fabricated via water-in-oil emulsion electrospinning. The sodium alginate concentration, water-to-oil ratio, and surfactant concentration were optimized for the maximum stability of the emulsion. The results demonstrated that an increasing water-to-oil ratio results in more deviation from Newtonian fluid and leads to a broader distribution of the fibers' diameters. Moreover, increasing poly(ε-caprolactone) concentration increases loss and storage moduli and increases the diameter of the resulting fibers. The nanofibers' characteristics were investigated by scanning electron microscopy, transmission electron microscopy, confocal laser scanning microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and water contact angle measurements. It was observed that using an emulsion composition of 10% (w/v) PCL and a water-to-oil ratio of 0.1 results in smooth, cylindrical, and uniform core/shell nanofibers with PCL in the shell and ALG in the core. The in vitro cell culture study demonstrated the favorable biocompatibility of nanofibers. Overall, this study provides a promising and trustworthy material for biomedical applications.